Recognizing structure in novel tunes: differences between human and rats - Paola Crespo-Bojorque; Elodie Cauvet; Christophe Pallier; Juan M. Toro (Animal Cognition)
Abstract A central feature in music is the hierarchical organization of its components. Musical pieces are not a simple concatenation of chords, but are characterized by rhythmic and harmonic structures. Here, we explore if sensitivity to music structure might emerge in the absence of any experience with musical stimuli. For this, we tested if rats detect the difference between structured and unstructured musical excerpts and compared their performance with that of humans. Structured melodies were excerpts of Mozart's sonatas. Unstructured melodies were created by the recombination of fragments of different sonatas. We trained listeners (both human participants and Long-Evans rats) with a set of structured and unstructured excerpts, and tested them with completely novel excerpts they had not heard before. After hundreds of training trials, rats were able to tell apart novel structured from unstructured melodies. Human listeners required only a few trials to reach better performance than rats. Interestingly, such performance was increased in humans when tonality changes were included, while it decreased to chance in rats. Our results suggest that, with enough training, rats might learn to discriminate acoustic differences differentiating hierarchical music structures from unstructured excerpts. More importantly, the results point toward species-specific adaptations on how tonality is processed.